Factors related to open defecation (babs) in the village of Cot Keumude, Kec. Woyla, West Aceh Regency year 2023 - Cut Mauliza; Safrizal; Ihsan Murdani; Maiza Duana (Sean Institute, 2023)
Indonesia is a country with a population that still practices open defecation in various open areas. According to WHO data, Indonesia is included in 61 countries in the world where more than 5% of the population still practice open defecation. In the case of open defecation, Aceh Province is classified as having the highest open defecation and data from the Ministry of Health states that out of 6502 villages where people still practice open defecation in open areas, only 3% of villages are free from open defecation in 2017. This has led to an increase in the spread of diarrheal disease in the Aceh region. The Aceh Provincial Health Office revealed that the impact of open defecation resulted in a high number of diarrhea sufferers reaching 256,386 people with an average of 13% per year. Cot Keumude Village, Woyla District, West Aceh District is one of the villages that still causes open defecation problems and is one of the villages where most people defecate in open areas. It is known that Cot Keumude Village is occupied by 76 family cards (KK), while 31 families have facilities that comply with the Ministry of Health standards and 46 families do not have facilities. This study aims to look at the factors associated with open defecation (BABS) behavior in Cot Keumude Village, Woyla District, West Aceh District. This study uses a descriptive quantitative research method with a cross sectional approach, while the univariate and bivariate analysis methods are through the chi square test. The results showed that the knowledge variable was p-value = 0.009, the support variable from community leaders was p-value = 0.000, the education variable was p-value = 0.001 and economic status was p-value = 0.001. These results indicate that the variables of knowledge, support from community leaders, education and economic status are significantly related to open defecation behavior in the village of Cot Keumude.